Índice de atividade dos fundos de investimento em ações: determinantes e consequências - Milan, Pedro Luiz Albertin Bono (2012)
This dissertation measures asset turnover in the Brazilian market for stock investment funds and the impact of this activity on the performance of the funds. In addition, seeks to highlight the determinants of turnover using the characteristics of the funds and their managers. The study follows Gaspar, Massa and Matos (2005) methodology of measuring turnover and uses Sharpe and Jensen Ratios for measuring fund performance. Using a database containing composition, returns, fund characteristics and manager, the dissertation shows that turnover negatively impacts the performance of the funds. The manager's age, educational background and market experience, are crucial to high levels of turnover.